Flow-cytometric analysis of human monocyte subsets targeted by Mycobacterium bovis BCG before granuloma formation. Issue 8 (16th November 2018) - Delcroix, Melaine; Heydari, Kartoosh; Dodge, Ren; Riley, Lee W
Abstract: Infection with Mycobacterium tuberculosis (Mtb) is characterized by an inflammatory response resulting in the formation of granulomas. These tight aggregates of immune cells play an important role in bacterial containment and in the eventual outcome of infection. Monocytes are a major component of the early immune response to Mtb and contribute to the cellular matrix of the newly forming granuloma. Therefore, defining which monocyte subset is the target of mycobacterial infection is critical. Here, we describe a flow-cytometry-based assay to analyze infectivity in vitro of monocyte subsets by Mycobacterium bovis BCG before granuloma formation. We identified CD14 + CD16 − monocytes as the main target of infection in peripheral blood mononuclear cells from six healthy donors. CD14 + CD16 + monocytes displayed the lowest infection rates and remained uninfected in some donors. We found that a longer infection time resulted in an increase of the percentage of monocytes infected and of the number of granulomas produced. We did not observe changes in monocyte cell death or subset expansion upon infection. Future experiments with our in vitro method could help define Mtb infectivity of monocyte subsets. Our study provides a platform to investigate how early infection of different monocyte subsets may alter granuloma formation and outcomes of Mtb infection. Abstract : This study examines the early interaction of a vaccine strain of Mycobacterium bovis (BCG) and immune cells in the formation of granulomas in vitro .